Preparation method and application of a carbon-based single-atom oxygen reduction reaction electrocatalyst
Through dynamic timing coordination regulation, gradual heating and coordination time control, chemical vapor etching and step-by-step calcination strategies, a carbon-based single-atom oxygen reduction electrocatalyst with FeN4/Fe2O3 active site structure with N-Fe-O bridge bond linkage solves the problem of structural conversion or removal of the catalyst at high potential, and significantly improves catalytic activity and stability.
Patent Information
- Application Number
- CN202411853624.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The existing carbon-based single-atom oxygen reduction electrocatalysts are prone to structural conversion or detachment under high potentials, resulting in inactivation of active sites, poor catalyst stability, and difficult to achieve the expected catalytic capacity.
The strategies of dynamic timing coordination regulation, gradual heating and coordination time control, chemical vapor phase etching and step-by-step calcination are adopted to stably form the FeN4/Fe2O3 active site structure with N-Fe-O bridge bond link and an oxygen reduction reaction electrocatalyst with rich pore structure.
The stability and accessibility of the active site are improved, the smooth progress of the oxygen reduction reaction is promoted, the catalytic activity and stability are significantly improved, and the selectivity of the 4-electron oxygen reduction reaction is achieved.
Smart Images

Figure CN119315046B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of oxygen reduction reaction electrocatalysts, and specifically relates to a preparation method and application of a highly active and highly stable carbon-based single-atom oxygen reduction reaction electrocatalyst. Background Art
[0002] Oxygen reduction reaction (ORR) is a key reaction in new energy devices such as fuel cells and metal-air batteries. In order to reduce catalyst costs and promote the further industrialization of ORR-based new energy devices, it is necessary to develop highly active and low-cost non-precious metal-based electrocatalysts as alternatives to expensive Pt-based catalysts.
[0003] At present, atomically dispersed Fe-NC catalysts are ideal for replacing Pt-based ORR catalysts. Due to the special electronic structure of transition metals, they exhibit severe Fenton reactions during the catalytic process. In this process, the 2-electron ORR reduces the catalytic efficiency and leads to significant Fe atom leaching, which ultimately manifests as rapid degradation of ORR-based new energy devices. In current research, there is hope that the axially coordinated single-atom structure that activates the OO bond activation and inhibits the generation of 2-electron ORR byproducts will still be transformed or directly removed at high potentials, leading to the inactivation of the ORR active site. Integrating axial ligands into cluster structures may be an effective strategy to prevent structural damage. The rich surface electrons of the cluster structure are also expected to be directed to single atoms through the axial N-Fe-O bridge bond, which is conducive to further enhancing the OO bond activation. However, the single-atom structure is highly dependent on the random generation during the calcination process, and it is often difficult to stably obtain the designed advantageous active site structure, resulting in the catalytic ability of the synthesized non-precious metal single-atom catalyst failing to achieve the expected goal.
[0004] Therefore, it is necessary to design a synthetic strategy to solve the technical defects of random generation of catalyst active site structure and its poor stability, which is the key to promote the further development of electrocatalytic technology. Summary of the invention
[0005] The present invention aims to solve the technical problem of the difficulty in the controllable preparation of carbon-based single-atom electrocatalysts, and provides a method for preparing a carbon-based single-atom oxygen reduction reaction electrocatalyst with high activity and stability. The method is based on the strategy of dynamic sequential coordination regulation, gradual heating and coordination time control, chemical vapor etching and step-by-step calcination to stably form FeN with N-Fe-O bridge bonds. 4 / Fe 2 O 3The oxygen reduction reaction electrocatalyst with an active site structure and rich pore structure provides an active site structure that is conducive to 4-electron ORR, improves the stability and accessibility of the active site, and promotes the smooth progress of ORR. The oxygen reduction reaction electrocatalyst with an advantageous active site structure and rich pore structure constructed by this method not only obtains excellent electrocatalytic activity, but also effectively solves the technical problems existing in the design and construction of single-atom active sites, and the constructed oxygen reduction reaction electrocatalyst exhibits excellent catalytic activity and catalytic stability.
[0006] The present invention adopts the following technical solutions to solve the above problems:
[0007] A method for preparing a carbon-based single-atom oxygen reduction reaction electrocatalyst, wherein the specific preparation process is as follows: dopamine-functionalized polypyrrole nanoparticles are used as a skeleton material, ethylenediaminetetraacetic acid (EDTA) and bipyridine (Bipy) are used as ligands, and a multi-level stably loaded complex with Fe-O and Fe-N coordination structures is formed on the skeleton material through dynamic timing ligand regulation, gradual temperature increase and coordination time control, and then the obtained complex-loaded polypyrrole nanoparticles are subjected to 200-300°C low-temperature pre-calcination, corrosive gas etching and 500-900°C high-temperature step-by-step calcination treatment to stably produce FeN linked by N-Fe-O bridge bonds. 4 / Fe 2 O 3 The active site structure is optimized, and a rich pore structure is obtained to optimize the contact between the electrolyte and the active sites, ultimately producing a carbon-based single-atom oxygen reduction reaction electrocatalyst.
[0008] A method for preparing a carbon-based single-atom oxygen reduction reaction electrocatalyst, the specific preparation steps of which are:
[0009] Step S1: dissolving pyrrole monomer and dopamine in deionized water, and then adding a polymerization initiator ammonium persulfate aqueous solution to react, and after the reaction, repeatedly centrifuging and washing the product with ethanol and deionized water until the supernatant is colorless, and freeze-drying to obtain dopamine functionalized polypyrrole nanoparticles;
[0010] Step S2: dispersing the dopamine functionalized polypyrrole nanoparticles obtained in step S1 in an ethylenediaminetetraacetic acid ligand solution, centrifugally separating and freeze-drying to obtain ethylenediaminetetraacetic acid-loaded polymer nanoparticles, and then dispersing the obtained ethylenediaminetetraacetic acid-loaded polymer nanoparticles in a bipyridine ligand solution, centrifugally separating and freeze-drying to obtain ethylenediaminetetraacetic acid and bipyridine ordered multi-level loaded polymer nanoparticles; the selected ethylenediaminetetraacetic acid ligand solution and bipyridine ligand solution can form a stable loaded complex through hydrogen bonding and π-π interaction with the dopamine functionalized polypyrrole nanoparticles, thereby ensuring the stability of the derived structure; the hierarchical loading treatment can ensure that the Fe-N coordination structure is formed in the outer layer, so that the derived FeN 4 The Fe-N and Fe-O coordination structures formed during the heat treatment are respectively derived into FeN 4 and Fe 2 O 3 , the interlayer N and O co-coordinated Fe atoms promote the formation of N-Fe-O bridge bond enhanced structure;
[0011] Step S3: The polymer nanoparticles loaded with ethylenediaminetetraacetic acid and bipyridine in an orderly multi-level manner obtained in step S2 are dispersed in a ferric acetate solution, and metal coordination is performed under the control of gradually increasing the temperature and coordination time. Specifically, the metal ions are firstly pre-coordinated with ethylenediaminetetraacetic acid in a low temperature coordination stage at 20-30°C for 1-3h. In this low temperature coordination stage, Fe 3+ It forms a large amount of Fe-O coordination structure with the hexadentate ligand EDTA, which has strong coordination ability, thus ensuring that sufficient Fe 2 O 3 As a performance enhancement structure; secondly, the medium temperature coordination stage at 60~80℃ for 20~40min promotes the formation of co-coordination of the two ligands. 3+ The coordination ability of FeN improves with the increase of temperature, forming a competitive coordination with EDTA, resulting in the formation of Fe-N and Fe-O co-coordination structure, which is conducive to the formation of FeN linked by N-Fe-O bridge bonds during the heat treatment process. 4 and Fe 2 O 3 To improve the ORR selectivity; finally, the catalyst was treated at a high temperature coordination stage of 90-110°C for 20-40 minutes to form a more stable coordination structure. This high temperature coordination stage formed a richer and more stable coordination structure, which can effectively improve the active site density of the target catalyst. Finally, the precursor was obtained by centrifugal collection and freeze drying.
[0012] Step S4: pre-sintering the precursor obtained in step S3 at a low temperature of 200-300° C. in a nitrogen atmosphere tube furnace, and then etching the pre-sintered product with a corrosive gas to obtain a pre-sintered etched product;
[0013] Step S5: sinter the pre-sintered etched product obtained in step S4 in an argon atmosphere in steps, specifically, sintering at 500-600°C for 0.5-2 hours to obtain the derived FeN 4 / Fe 2 O 3 Active site structure, and then sintered at 800~900℃ for 1~3h to further stabilize FeN 4 The structure of Fe 2 O 3 The ordered crystal structure ultimately yields a carbon-based single-atom oxygen reduction reaction electrocatalyst.
[0014] It is further defined that the mass ratio of dopamine to pyrrole in step S1 is 0.04-0.06:1.
[0015] It is further defined that the feed ratio of dopamine functionalized polypyrrole nanoparticles, ethylenediaminetetraacetic acid and bipyridine in step S2 is 5 g: 1~2 mol: 1~2 mol.
[0016] It is further defined that the specific process of etching in step S4 is: placing ammonium chloride and the pre-sintered product at the air inlet and air outlet of a nitrogen atmosphere tubular furnace respectively, and using the corrosive gas released by the decomposition of ammonium chloride under low temperature conditions of 200~300°C to etch the pre-sintered product to obtain a pre-sintered etching precursor.
[0017] A carbon-based single-atom oxygen reduction reaction electrocatalyst is used as an oxygen reduction reaction electrocatalyst in new energy devices.
[0018] It is further defined that the new energy device is a fuel cell or a metal-air battery.
[0019] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0020] 1. The present invention uses dopamine to functionalize the surface of polypyrrole nanoparticles. The hydroxyl and amino groups introduced on the surface of the polypyrrole nanoparticles can form hydrogen bonds with the carboxyl groups in EDTA. The pyrrole structure itself can form π-π conjugation with Bipy, ensuring a strong interaction between the polypyrrole nanoparticles and the two ligands, thereby achieving the formation of a stable EDTA and Bipy load during the synthesis process.
[0021] 2. The dynamic sequential ligand pretreatment of the present invention is conducive to the formation of multi-level complexes of EDTA and Bipy, and promotes the formation of Fe-N and Fe-O coordination structures with adjustable ratios as FeN4 and Fe 2 O 3 The precursor of the structure effectively builds FeN 4 / Fe 2 O 3 The Fe atoms coordinated with EDTA and Bipy layers have both Fe-N and Fe-O coordination, and FeN is derived by heat treatment. 4 and Fe 2 O 3 The N-Fe-O bridge structure between the FeN 4 As the ORR active center appears on the outer side of the catalyst, the FeN 4 The contact with reactants increases the density of accessible active sites.
[0022] 3. In the process of gradually increasing temperature and controlling coordination time, Fe 3+ After addition, it first forms a complex with the hexadentate ligand EDTA with strong coordination ability in the ligand layer on the surface of polypyrrole nanoparticles to derive sufficient Fe 2 O 3 , Bipy and Fe 3+ The coordination ability of N and O is enhanced, forming a competitive coordination with EDTA, ensuring the presence of a large number of N and O co-coordinated Fe atoms, thereby promoting the formation of N-Fe-O bridge bond reinforcement structure, and raising the temperature again to promote the full reaction of metal ions and ligands.
[0023] 4. The preliminary calcination and chemical vapor etching process at low temperature in the present invention not only initially forms FeN 4 , Fe 2 O 3 The N-Fe-O bridge bond structure avoids the disordered aggregation of metals caused by direct heating, and also creates pores on the surface to make the internal FeN 4 The active sites are exposed, which improves the catalytic ability of the final target catalyst. The further medium-temperature calcination process effectively promotes the FeN 4 / Fe 2 O 3 The formation of a stable structure, high temperature calcination not only further stabilizes the single atomic configuration, but also destroys the crystalline Fe formed by medium temperature calcination. 2 O 3 , the amorphous Fe 2 O 3 The clusters have more abundant surface electrons, which are injected into FeN through N-Fe-O bridge bonds. 4 , which stimulates the effective activation of the OO bond.
[0024] In summary, the highly active and highly stable carbon-based single-atom oxygen reduction reaction electrocatalyst constructed by the present invention successfully forms a highly accessible FeN 4 / Fe 2 O 3 The active site structure stimulates the activation of the OO bond in the ORR process and creates a pore structure that promotes effective contact between the reactants and the active sites, which is conducive to obtaining excellent ORR catalytic activity and catalytic stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 LSV diagrams of the electrocatalysts prepared in Example 1 and Comparative Examples 1 to 6;
[0026] Figure 2 XRD patterns of the electrocatalysts prepared in Example 1 and Comparative Examples 1-6. DETAILED DESCRIPTION
[0027] The present invention obtains a precursor with controllable Fe-N and Fe-O coordination structures by dynamic sequential ligand pretreatment, gradual temperature increase and coordination time control. 3+ First, a large amount of Fe-O coordination structure is formed with EDTA to derive sufficient Fe 2 O 3 As a performance enhancement structure; in the medium temperature coordination stage (70℃), Bipy and Fe 3+ The coordination ability of Fe-N is enhanced to form competitive coordination with EDTA, resulting in the formation of Fe-N and Fe-O co-coordination structure, which is conducive to the formation of FeN linked by N-Fe-O bridge bonds during heat treatment. 4 and Fe 2 O 3 To improve ORR selectivity; the final high-temperature coordination stage (100°C) formed a richer and more stable coordination structure; further low-temperature etching and step-by-step calcination formed FeN linked by N-Fe-O bridge bonds. 4 \Fe 2 O 3 Active site structure. This strategy effectively solves the problem of random generation of single-atom active site structure and achieves excellent activity and 4-electron ORR selectivity.
[0028] In order to better illustrate the above technical solution, the above technical solution will be described in detail below in conjunction with specific embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments, and all technologies implemented based on the above content of the present invention belong to the scope of the present invention. Example 1
[0029] Step S1: 2 g of pyrrole and 0.1 g of dopamine are dispersed in 100 mL of deionized water as a monomer solution, and 5 g of ammonium persulfate is dissolved in 100 mL of deionized water as a polymerization initiator. The polymerization initiator is quickly added to the monomer solution at 25° C. and stirred for 6 hours. After the reaction, the product is repeatedly washed with ethanol and deionized water, centrifuged, and freeze-dried to obtain dopamine-functionalized polypyrrole nanoparticles;
[0030] Step S2: ultrasonically dispersing 0.5 g of the dopamine functionalized polypyrrole nanoparticles obtained in step S1 in an EDTA solution (0.1 mol), stirring at 25° C. for 2 h, centrifuging, and freeze-drying to obtain EDTA-modified polymer nanoparticles, and then ultrasonically dispersing the obtained product in a Bipy solution (0.1 mol) to perform the same loading operation process, and finally obtaining EDTA and Bipy multi-layered polymer nanoparticles after freeze-drying again;
[0031] Step S3: ultrasonically disperse the polymer nanoparticles loaded with EDTA and Bipy obtained in step S2 in 100 mL of 0.02 M ferric acetate solution, stir at 25° C. for 2 h to complete the pre-coordination reaction between the metal ions and EDTA, then increase the temperature to 70° C. and maintain for 30 min to promote the formation of co-coordination of the two ligands, and finally increase the temperature to 100° C. and maintain for 30 min to form a more stable coordination structure, and finally freeze-dry to obtain the precursor to be heat-treated;
[0032] Step S4: pre-sintering the precursor obtained in step S3 at 250° C. for 1 h in a nitrogen atmosphere, and then placing 3 g of ammonium chloride and the pre-sintered product at the air inlet and air outlet of a nitrogen atmosphere tubular furnace respectively, heating to 250° C. and maintaining for 1 h, and etching the pre-sintered product using the corrosive gas released by the decomposition of ammonium chloride to obtain a pre-sintered etched product;
[0033] Step S5: The pre-sintered etched product obtained in step S4 is calcined in a tubular furnace in an argon atmosphere by stepwise heating, specifically, firstly heating to 500° C. and maintaining for 1 h to obtain FeN 4 / Fe 2 O 3 The target structure was further stabilized by heating to 900 °C for 2 h. 4 The structure of Fe 2 O 3 Ordered crystal configuration to obtain optimized electrocatalytic ability, and ultimately produce a carbon-based single-atom oxygen reduction reaction electrocatalyst.
[0034] Comparative Example 1 (without dopamine functionalization)
[0035] Step S1: 2 g of pyrrole is dispersed in 100 mL of deionized water as a monomer solution, and 5 g of ammonium persulfate is dissolved in 100 mL of deionized water as a polymerization initiator. The polymerization initiator is quickly added to the monomer solution at 25° C. and stirred for 6 hours. After the reaction is completed, the product is repeatedly washed with ethanol and deionized water, centrifuged, and freeze-dried to obtain polypyrrole nanoparticles;
[0036] Step S2: ultrasonically dispersing 0.5 g of the polypyrrole nanoparticles obtained in step S1 in an EDTA solution (0.1 mol), stirring at 25° C. for 2 h, centrifuging, and freeze-drying to obtain EDTA-modified polymer nanoparticles, and ultrasonically dispersing the obtained product in a Bipy solution (0.1 mol) again to perform the same loading operation process, and finally obtaining EDTA and Bipy multi-layered polymer nanoparticles after freeze-drying again;
[0037] Step S3: ultrasonically disperse the polymer nanoparticles loaded with EDTA and Bipy obtained in step S2 in 100 mL of 0.02 M ferric acetate solution, stir at 25° C. for 2 h to complete the pre-coordination reaction between the metal ions and EDTA, then increase the temperature to 70° C. and maintain for 30 min to promote the formation of co-coordination of the two ligands, and finally increase the temperature to 100° C. and maintain for 30 min to form a more stable coordination structure, and finally freeze-dry to obtain the precursor to be heat-treated;
[0038] Step S4: pre-sintering the precursor obtained in step S3 at 250° C. for 1 h in a nitrogen atmosphere, and then placing 3 g of ammonium chloride and the pre-calcined product at the air inlet and air outlet of a nitrogen atmosphere tubular furnace, respectively, heating to 250° C. and maintaining for 1 h, and etching using the corrosive gas released by the decomposition of ammonium chloride to obtain a pre-sintered etched product;
[0039] Step S5: The pre-sintered etched product obtained in step S4 is calcined in a tubular furnace in an argon atmosphere in steps, specifically, firstly heated to 500° C. and maintained for 1 hour, and then heated to 900° C. and maintained for 2 hours to obtain an electrocatalyst.
[0040] Comparative Example 2 (without adding EDTA)
[0041] Step S1: 2 g of pyrrole and 0.1 g of dopamine are dispersed in 100 mL of deionized water as a monomer solution, and 5 g of ammonium persulfate is dissolved in 100 mL of deionized water as a polymerization initiator. The polymerization initiator is quickly added to the monomer solution at 25° C. and stirred for 6 hours. After the reaction, the product is repeatedly washed with ethanol and deionized water, centrifuged, and freeze-dried to obtain dopamine-functionalized polypyrrole nanoparticles;
[0042] Step S2: 0.5 g of the dopamine functionalized polypyrrole nanoparticles obtained in step S1 were ultrasonically dispersed in a Bipy solution (0.1 mol), stirred at 25° C. for 2 h, centrifuged, and freeze-dried to obtain Bipy-modified polymer nanoparticles;
[0043] Step S3: ultrasonically dispersing the Bipy-modified polymer nanoparticles obtained in step S2 in 100 mL of 0.02 M ferric acetate solution, stirring at 25° C. for 2 h, then raising the temperature to 70° C. and maintaining it for 30 min, and finally raising the temperature to 100° C. and maintaining it for 30 min to form a stable coordination structure, and finally freeze-drying to obtain a precursor to be heat-treated;
[0044] Step S4: pre-sintering the precursor obtained in step S3 at 250° C. for 1 h in a nitrogen atmosphere, and then placing 3 g of ammonium chloride and the pre-sintered product at the air inlet and air outlet of a nitrogen atmosphere tubular furnace, respectively, heating to 250° C. and maintaining for 1 h, and etching using the corrosive gas released by the decomposition of ammonium chloride to obtain a pre-sintered etched product;
[0045] Step S5: The pre-sintered etched product obtained in step S4 is calcined in a tubular furnace with an argon atmosphere in steps, firstly heated to 500° C. and maintained for 1 hour, and then heated to 900° C. and maintained for 2 hours to obtain an electrocatalyst.
[0046] Comparative Example 3 (without hierarchical ligand pretreatment)
[0047] Step S1: 2 g of pyrrole and 0.1 g of dopamine are dispersed in 100 mL of deionized water as a monomer solution, and 5 g of ammonium persulfate is dissolved in 100 mL of deionized water as a polymerization initiator. The polymerization initiator is quickly added to the monomer solution at 25° C. and stirred for 6 hours. After the reaction, the product is repeatedly washed with ethanol and deionized water, centrifuged, and freeze-dried to obtain dopamine-functionalized polypyrrole nanoparticles;
[0048] Step S2: ultrasonically dispersing 0.5 g of the dopamine functionalized polypyrrole nanoparticles obtained in step S1 in a solution containing 0.1 mol EDTA and 0.1 mol Bipy, stirring at 25° C. for 2 h, centrifuging, and freeze-drying to obtain EDTA and Bipy loaded polymer nanoparticles;
[0049] Step S3: ultrasonically dispersing the EDTA and Bipy-loaded polymer nanoparticles obtained in step S2 in 100 mL of 0.02 M ferric acetate solution, stirring at 25° C. for 2 h to complete the pre-coordination reaction between the metal ions and EDTA, then raising the temperature to 70° C. for 30 min to promote the formation of co-coordination of the two ligands, and finally raising the temperature to 100° C. for 30 min to form a more stable coordination structure, and finally freeze-drying to obtain the precursor to be heat-treated;
[0050] Step S4: pre-sintering the precursor obtained in step S3 at 250° C. for 1 h in a nitrogen atmosphere, and then placing 3 g of ammonium chloride and the pre-sintered product at the air inlet and air outlet of a nitrogen atmosphere tubular furnace, respectively, heating to 250° C. and maintaining for 1 h, and etching using the corrosive gas released by the decomposition of ammonium chloride to obtain a pre-sintered etched product;
[0051] Step S5: The pre-sintered etched product obtained in step S4 is calcined in a tubular furnace with an argon atmosphere in steps, firstly heated to 500° C. and maintained for 1 hour, and then heated to 900° C. and maintained for 2 hours to obtain an electrocatalyst.
[0052] Comparative Example 4 (without gradual heating and coordination time control)
[0053] Step S1: 2 g of pyrrole and 0.1 g of dopamine are dispersed in 100 mL of deionized water as a monomer solution, and 5 g of ammonium persulfate is dissolved in 100 mL of deionized water as a polymerization initiator. The polymerization initiator is quickly added to the monomer solution at 25° C. and stirred for 6 hours. After the reaction, the product is repeatedly washed with ethanol and deionized water, centrifuged, and freeze-dried to obtain dopamine-functionalized polypyrrole nanoparticles;
[0054] Step S2: ultrasonically disperse 0.5 g of the dopamine functionalized polypyrrole nanoparticles obtained in step S1 in an EDTA solution (0.1 mol), stir at 25°C for 2 h, centrifuge and freeze-dry to obtain EDTA-modified polymer nanoparticles, and ultrasonically disperse the obtained product in a Bipy solution (0.1 mol) again to perform the same loading operation process, and freeze-dry again to obtain EDTA and Bipy multi-layered polymer nanoparticles;
[0055] Step S3: ultrasonically dispersing the EDTA and Bipy multi-layered polymer nanoparticles obtained in step S2 in 100 mL of 0.02 M ferric acetate solution, stirring at 25° C. for 2 h to form a coordination structure, and then freeze-drying to obtain a precursor to be heat-treated;
[0056] Step S4: pre-sintering the precursor obtained in step S3 at 250° C. for 1 h in a nitrogen atmosphere, and then placing 3 g of ammonium chloride and the pre-sintered product at the air inlet and air outlet of a nitrogen atmosphere tubular furnace, respectively, heating to 250° C. and maintaining for 1 h, and etching using the corrosive gas released by the decomposition of ammonium chloride to obtain a pre-sintered etched product;
[0057] Step S5: The pre-sintered etched product obtained in step S4 is calcined in a tubular furnace with an argon atmosphere in steps, specifically, firstly heated to 500° C. and maintained for 1 hour, and then heated to 900° C. and maintained for 2 hours to obtain an electrocatalyst.
[0058] Comparative Example 5 (without using ammonium chloride)
[0059] Step S1: 2 g of pyrrole and 0.1 g of dopamine are dispersed in 100 mL of deionized water as a monomer solution, and 5 g of ammonium persulfate is dissolved in 100 mL of deionized water as a polymerization initiator. The polymerization initiator is quickly added to the monomer solution at 25° C. and stirred for 6 hours. After the reaction, the product is repeatedly washed with ethanol and deionized water, centrifuged, and freeze-dried to obtain dopamine-functionalized polypyrrole nanoparticles;
[0060] Step S2: ultrasonically disperse 0.5 g of the dopamine functionalized polypyrrole nanoparticles obtained in step S1 in an EDTA solution (0.1 mol), stir at 25°C for 2 h, centrifuge and freeze-dry to obtain EDTA-modified polymer nanoparticles, and ultrasonically disperse the obtained product in a Bipy solution (0.1 mol) again to perform the same loading operation process, and freeze-dry again to obtain EDTA and Bipy multi-layered polymer nanoparticles;
[0061] Step S3: ultrasonically disperse the EDTA and Bipy multi-layered polymer nanoparticles obtained in step S2 in 100 mL of 0.02 M ferric acetate solution, stir at 25° C. for 2 h to complete the pre-coordination reaction between the metal ions and EDTA, then increase the temperature to 70° C. and maintain for 30 min to promote the formation of co-coordination of the two ligands, and finally increase the temperature to 100° C. and maintain for 30 min to form a more stable coordination structure, and then freeze-dry to obtain the precursor to be heat-treated;
[0062] Step S4: pre-sintering the precursor obtained in step S3 at 250° C. for 2 h in a nitrogen atmosphere to obtain a pre-sintered product;
[0063] Step S5: The pre-sintered product obtained in step S4 is calcined in a tubular furnace with an argon atmosphere in steps, specifically, firstly heated to 500° C. and maintained for 1 hour, and then heated to 900° C. and maintained for 2 hours to obtain an electrocatalyst.
[0064] Comparative Example 6 (directly heating to 900°C for calcination)
[0065] Step S1: 2 g of pyrrole and 0.1 g of dopamine are dispersed in 100 mL of deionized water as a monomer solution, and 5 g of ammonium persulfate is dissolved in 100 mL of deionized water as a polymerization initiator. The polymerization initiator is quickly added to the monomer solution at 25° C. and stirred for 6 hours. After the reaction, the product is repeatedly washed with ethanol and deionized water, centrifuged, and freeze-dried to obtain dopamine-functionalized polypyrrole nanoparticles;
[0066] Step S2: ultrasonically disperse 0.5 g of the dopamine functionalized polypyrrole nanoparticles obtained in step S1 in an EDTA solution (0.1 mol), stir at 25°C for 2 h, centrifuge and freeze-dry to obtain EDTA-modified polymer nanoparticles, and ultrasonically disperse the obtained product in a Bipy solution (0.1 mol) again to perform the same loading operation process, and freeze-dry again to obtain EDTA and Bipy multi-layered polymer nanoparticles;
[0067] Step S3: ultrasonically disperse the EDTA and Bipy multi-layered polymer nanoparticles obtained in step S2 in 100 mL of 0.02 M ferric acetate solution, stir at 25° C. for 2 h to complete the pre-coordination reaction between the metal ions and EDTA, then increase the temperature to 70° C. and maintain for 30 min to promote the formation of co-coordination of the two ligands, and finally increase the temperature to 100° C. and maintain for 30 min to form a more stable coordination structure, and then freeze-dry to obtain the precursor to be heat-treated;
[0068] Step S4: pre-sintering the precursor obtained in step S3 at 250° C. for 1 h in a nitrogen atmosphere, and then placing 3 g of ammonium chloride and the pre-sintered product at the air inlet and air outlet of a nitrogen atmosphere tubular furnace, respectively, heating to 250° C. and maintaining for 1 h, and etching using the corrosive gas released by the decomposition of ammonium chloride to obtain a pre-sintered etched product;
[0069] Step S5: calcining the pre-sintered etched product obtained in step S4 at 900° C. for 2 h in an argon atmosphere tubular furnace to obtain an electrocatalyst.
[0070] The electrocatalyst prepared in Example 1 of the present invention has good ORR electrocatalytic performance. Figure 1 It can be seen from the electrical performance test results that the electrocatalyst prepared in Example 1 exhibits the best half-wave potential (0.94 V). In Comparative Example 1, dopamine functionalization was not used, and effective Fe loading could not be formed, showing the worst half-wave potential (0.79 V). Comparative Examples 2, 3, and 4 were all unable to effectively form FeN 4 / Fe 2 O 3The special structure showed undesirable half-wave potentials of 0.92V, 0.90V and 0.89V respectively. In Comparative Example 5, no ammonium chloride etching was performed, and a pore structure that promoted the contact between the active site and the electrolyte could not be formed, and the half-wave potential was low (0.85V). In Comparative Example 6, the direct heating and calcination caused part of the Fe-N coordinated metal in the precursor to aggregate into an inactive aggregate state, and thus showed a poor half-wave potential (0.88V).
[0071] By analyzing Example 1 and Comparative Examples 1 to 6, it can be concluded that key factors such as dopamine functionalization, dynamic sequential ligand pretreatment, gradual temperature rise setting, coordination time control, gas phase etching and step-by-step calcination can all have different degrees of influence on the final half-wave potential. This shows that the present invention can significantly improve the catalytic performance and catalytic stability of the electrocatalyst by regulating the hydrogen bonds, coordination forms, pore structures and metal atom aggregation forms during the electrocatalyst synthesis process.
[0072] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.
Claims
1. A method for preparing a carbon-based single-atom oxygen reduction reaction electrocatalyst, characterized in that The specific preparation process is as follows: dopamine functionalized polypyrrole nanoparticles are used as the skeleton material, ethylenediaminetetraacetic acid and bipyridine are used as ligands, and a multi-level stable loaded complex with Fe-O and Fe-N coordination structure is formed on the skeleton material through dynamic timing ligand regulation, gradual temperature increase and coordination time control. The obtained complex-loaded polypyrrole nanoparticles are then subjected to low-temperature pre-calcination at 200-300°C, corrosive gas etching and high-temperature step-by-step calcination at 500-900°C to stably produce the FeN4 / Fe2O3 active site structure linked by N-Fe-O bridge bonds, and at the same time obtain a rich pore structure to optimize the contact between the electrolyte and the active site, and finally obtain a carbon-based single-atom oxygen reduction reaction electrocatalyst; The specific preparation steps are: Step S1: dissolving pyrrole monomer and dopamine in deionized water, and then adding a polymerization initiator ammonium persulfate aqueous solution to react, and after the reaction, repeatedly centrifuging and washing the product with ethanol and deionized water until the supernatant is colorless, and freeze-drying to obtain dopamine functionalized polypyrrole nanoparticles; Step S2: dispersing the dopamine functionalized polypyrrole nanoparticles obtained in step S1 in an ethylenediaminetetraacetic acid ligand solution, centrifugally separating and freeze-drying to obtain ethylenediaminetetraacetic acid-loaded polymer nanoparticles, and then dispersing the obtained ethylenediaminetetraacetic acid-loaded polymer nanoparticles in a bipyridine ligand solution, centrifugally separating and freeze-drying to obtain ethylenediaminetetraacetic acid and bipyridine ordered multi-level loaded polymer nanoparticles; the selected ethylenediaminetetraacetic acid ligand solution and bipyridine ligand solution can form a stable loaded complex through hydrogen bonding and π-π interaction with the dopamine functionalized polypyrrole nanoparticles, thereby ensuring the stability of the derived structure; the hierarchical loading treatment can ensure that the Fe-N coordination structure is formed in the outer layer, so that the derived FeN4 is fully exposed to the electrolyte to enhance the catalytic ability; the formed Fe-N and Fe-O coordination structures are derived into FeN4 and Fe2O3 respectively during heat treatment, and the interlayer N and O co-coordinated Fe atoms promote the formation of the N-Fe-O bridge bond enhanced structure; Step S3: The polymer nanoparticles loaded with ethylenediaminetetraacetic acid and bipyridine in an orderly multi-level manner obtained in step S2 are dispersed in a ferric acetate solution, and metal coordination is performed under the control of gradually increasing the temperature and coordination time. Specifically, the metal ions are firstly pre-coordinated with ethylenediaminetetraacetic acid in a low temperature coordination stage at 20-30°C for 1-3h. In this low temperature coordination stage, Fe 3+ The Fe-O coordination structure is formed with the hexadentate ligand ethylenediaminetetraacetic acid with strong coordination ability, thereby ensuring that sufficient Fe2O3 can be derived as a performance-enhancing structure; secondly, the coordination stage at 60-80℃ for 20-40min promotes the formation of co-coordination of the two ligands. 3+ The coordination ability of Fe-N and Fe-O improves with the increase of temperature, forming competitive coordination with ethylenediaminetetraacetic acid, resulting in the formation of Fe-N and Fe-O co-coordination structures, which helps to form FeN4 and Fe2O3 linked by N-Fe-O bridge bonds during the heat treatment process to improve the ORR selectivity; finally, it is treated at a high temperature coordination stage of 90-110℃ for 20-40min to form a more stable coordination structure. This high temperature coordination stage forms a richer and more stable coordination structure, which can effectively improve the active site density of the target catalyst, and finally the precursor is obtained by centrifugal collection and freeze drying; Step S4: pre-sintering the precursor obtained in step S3 at a low temperature of 200-300° C. in a nitrogen atmosphere tube furnace, and then etching the pre-sintered product with a corrosive gas to obtain a pre-sintered etched product; Step S5: The pre-sintered etched product obtained in step S4 is sintered in steps under an argon atmosphere, specifically, first sintered at 500-600°C for 0.5-2 hours to obtain a derived FeN4 / Fe2O3 active site structure, and then sintered at 800-900°C for 1-3 hours to further stabilize the FeN4 structure while breaking the ordered crystal structure of Fe2O3, and finally obtaining a carbon-based single-atom oxygen reduction reaction electrocatalyst.
2. The method for preparing a carbon-based single-atom oxygen reduction reaction electrocatalyst according to claim 1, characterized in that: The mass ratio of dopamine to pyrrole in step S1 is 0.04-0.06:
1.
3. The method for preparing a carbon-based single-atom oxygen reduction reaction electrocatalyst according to claim 1, characterized in that: The feed ratio of dopamine functionalized polypyrrole nanoparticles, ethylenediaminetetraacetic acid and bipyridine in step S2 is 5 g: 1-2 mol: 1-2 mol.
4. The method for preparing a carbon-based single-atom oxygen reduction reaction electrocatalyst according to claim 1, characterized in that The specific process of etching in step S4 is: placing ammonium chloride and the pre-sintered product at the air inlet and air outlet of a nitrogen atmosphere tubular furnace respectively, and etching the pre-sintered product using the corrosive gas released by the decomposition of ammonium chloride at a low temperature of 200-300°C to obtain a pre-sintered etched product.
5. Use of the carbon-based single-atom oxygen reduction reaction electrocatalyst according to claim 1 as an oxygen reduction reaction electrocatalyst for new energy devices.
6. The use according to claim 5, characterized in that: The new energy device is a fuel cell or a metal-air battery.
Citation Information
Patent Citations
Cobalt nanoparticle-loaded yeast carbon-based electrocatalyst as well as preparation and application thereof
CN115347197A
Atomically dispersed platinum-group metal-free catalysts and method for synthesis of the same
WO2022109337A1